Pengembangan Aplikasi Perangkat Bergerak "Tahu Kediri" Informasi Wisata Kediri Dengan Metode Human Centered Design - Muhamad Habib; Agi Putra Kharisma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Kediri has a variety of tourist attractions. The local government plans to develop the Smart City Concept in the city of Kediri. The development of Smart City in Kediri has one goal, namely Smart Branding. Smart Branding is introducing smart areas. If Smart Branding goes well, many tourists will visit. Not yet presenting tourism in Kediri has not been conveyed properly because Kediri does not yet have a special application. Therefore, in this final project a Kediri travel information mobile application will be developed under the name Tahu Kediri. Tahu Kediri because Kediri is a famous culinary, which is Tofu and Kediri travel information application. The application development uses the Human Centered Design design method. By using this method, the author can use the interface with the application for prospective users. The reason the authors developed the Tahu Kediri mobile application to help Kediri realize Smart Branding. In this application there are two Android sub application applications and Website applications. In the Tahu Kediri application, validation, usability and compatibility tests are performed.